Usage of languages in Pabradė (based on public notices) - Gruodytė, Joana (Taikomoji kalbotyra, 2016)
This article presents a quantitative study of public notices in Pabradė. It continues the research of the linguistic landscape of Pabradė started in 2008. The data has been collected by taking pictures of different texts in the public spaces of the area. The analysis focuses on the languages used (in their written form) in this small (population 5,542) multinational town. Pabradė is home to more than five nationalities, with Poles constituting the largest ethnic group (42.5%). In 2015, pictures of public notices on five of the town’s bulletin boards and in other places were taken three times (in January, May, and December). At first, the pictures of all notices were taken; then 400 different notices were selected. The material was classified according to the method of execution (handwritten, typewritten, handwritten/typewritten), the language of the notice, the number and sequence of the languages used (in multilingual notices). The languages were then verified for prevalence and the way such prevalence was manifested.The town’s monolingual notices are mostly written in Lithuanian, Russian, and Polish; some notices are bilingual and trilingual. A count of notices written in the languages of the ethnic groups residing in the town has shown that notices in Lithuanian prevail, whereas those in Polish constitute the smallest number. The analysis of language importance in bilingual and trilingual notices has also revealed a unique position of the Lithuanian (state) language: it is the language most frequently employed in the notices; it is used in all bilingual and trilingual notices.The studies of the texts (graffiti and notices on the bridges) photographed in 2008 and 2015 revealed very similar tendencies: texts in Lithuanian prevail, texts in Polish constitute an absolute minority, and the proportion of texts in Russian is similar (10.7% and 15.5%, respectively). The only difference was identified in the number of texts written in English. It is used more often in graffiti on bridges than in other notices in the town. Apparently, this is due to the difference in the age of their authors and potential readers of such texts; it also depends on the purpose of writing.
Keywords: linguistic landscape; public notices in Pabradė; monolingual notice; multilingual notice; language choice; dominant language